Computed tomography and magnetic resonance cholangiopancreatography in the assessment of acute pancreatitis - Korkut, Mustafa; Bedel, Cihan; Erman, Kursat; Yavuz, Alpaslan; Ulgen, Sinan; Avci, Ali (Universa Medicina, 2020)
BACKGROUNDAcute pancreatitis (AP) is a disease associated with sudden onset of abdominal and back pain in a band-like pattern, nausea, and vomiting. In patients with AP, the gold standard, i.e., the initial imaging modality to be used is ultrasonography (US). However, in cases where evaluation is insufficient, computed tomography (CT) and magnetic resonance cholangiopancreatography (MRCP) are other modalities to be applied. In this study, we aimed to demonstrate the diagnostic accuracy of CT and MRCP in patients with acute pancreatitis. METHODSSeventy-five patients diagnosed with acute pancreatitis were evaluated using CT and, as well as patients who underwent contrast-enhanced MRCP within 48 hours. CT and MRCP were examined in terms of the biliary tract and pancreatic duct structure, gallbladder, common bile duct stones and complications. Chi-square test and the Mann-Whitney U test were used to analyze the data at significance level of p<0.05. RESULTSOf all the included patients, 44 were male (58.7%), and the mean age was 59.27 Â± 17.37 years. In CT findings, the percentage of AP complication findings such as pancreatic necrosis, extrapancreatic complications, the pancreatic or peripancreatic fluid collection was significantly higher than the MRCP group (p<0.05). MRCP showed biliary tract findings such as cholelithiasis, gallstone, common bile duct dilatation, intrahepatic bile duct dilatation, choledochal stone and pancreatic duct dilatation at a higher percentage than CT. CONCLUSIONMRCP was superior to CT in gallbladder and choledochal stone and biliary tract dilatation but not in AP complications. Therefore, non-invasive and radiation-free MRCP can be used more widely in AP patients, especially in emergency departments.